2021
DOI: 10.1126/sciadv.abg1921
|View full text |Cite
|
Sign up to set email alerts
|

Environmental vulnerability of the global ocean epipelagic plankton community interactome

Abstract: Marine plankton form complex communities of interacting organisms at the base of the food web, which sustain oceanic biogeochemical cycles and help regulate climate. Although global surveys are starting to reveal ecological drivers underlying planktonic community structure and predicted climate change responses, it is unclear how community-scale species interactions will be affected by climate change. Here, we leveraged Tara Oceans sampling to infer a global ocean cross-domain plankton co-occurrence network—th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
64
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(94 citation statements)
references
References 127 publications
(124 reference statements)
13
64
0
3
Order By: Relevance
“…We found the potential implication of IBPs and antifreeze proteins with a differential expression suggesting tight coupling between cold temperature adaptation and salinity, in keeping with higher salinities lowering the freezing point of water. Such adaptations are consistent with a recent global ocean interactome study of plankton by Chaffron et al 66 , which found that Arctic planktonic communities are fundamentally different from temperate and tropical marine communities. The pelagophyte used for this experiment has only ever been found in the Arctic 22 adding weight to the notion that Arctic marine microbial eukaryotes may be genetically primed to be adapted to or at least able to cope with the broad range of salinities found in Arctic surface waters 67 .…”
Section: Discussionsupporting
confidence: 91%
“…We found the potential implication of IBPs and antifreeze proteins with a differential expression suggesting tight coupling between cold temperature adaptation and salinity, in keeping with higher salinities lowering the freezing point of water. Such adaptations are consistent with a recent global ocean interactome study of plankton by Chaffron et al 66 , which found that Arctic planktonic communities are fundamentally different from temperate and tropical marine communities. The pelagophyte used for this experiment has only ever been found in the Arctic 22 adding weight to the notion that Arctic marine microbial eukaryotes may be genetically primed to be adapted to or at least able to cope with the broad range of salinities found in Arctic surface waters 67 .…”
Section: Discussionsupporting
confidence: 91%
“…Hence, although limited by single time points or “snapshot” sampling, combining these measurements with a robust statistical framework (i.e., network-based, cross-validated, multivariate-aware correlation analysis) enables statistical exploration to establish hypotheses about key ecosystem players. For this, we can leverage the context of hypothesized interactions ( 25 ) instead of using the more traditional pairwise correlations (e.g., of a member of specific taxon and an ecosystem output) from classical studies.…”
Section: Discussionmentioning
confidence: 99%
“…S2, E and F) and selects for cold-adapted communities in polar regions. A temperature-driven RNA virus community composition complements that for dsDNA viruses ( 21 ), prokaryotes ( 22 ), eukaryotes ( 24 ), and their interactions ( 25 ).…”
Section: Rna Virus Meta-community Analyses Reveal Distinct Ecological...mentioning
confidence: 98%
See 1 more Smart Citation
“…Among these are increased water temperature and stratification, nutrient paucity and acidification (Bopp et al 2013). Moreover, a recent study indicated that numerous important diatom genera, such as Chaetoceros, Porosira and Proboscia , are predicted to be vulnerable to climate change, particularly in polar plankton communities (Chaffron et al 2021). Diatoms appear therefore to be valuable candidates to investigate the fundamental links between their genomes, physiology and population dynamics, in light of predicted environmental changes.…”
Section: Introductionmentioning
confidence: 99%